Computational Tool to Support Design of DAC Converter Model AD7528 with the Object Code in XML - Almeida, Tiago da Silva; Silva, Alexandre Cesar R. da; Sampaio, Daniel J. B. S. (2012 IEEE Electronics, Robotics and Automotive Mechanics Conference, 2012)
Based on literature review, electronic systems design employ largely top-down methodology. The top-down methodology is vital for success in the synthesis and implementation of electronic systems. In this context, this paper presents a new computational tool, named BD^2XML, to support electronic systems design. From a block diagram system of mixed-signal is generated object code in XML markup language. XML language is interesting because it has great flexibility and readability. The BD^2XML was developed with object-oriented paradigm. It was used the AD7528 converter modeled in MATLAB / Simulink as a case study. The MATLAB / Simulink was chosen as a target due to its wide dissemination in academia and industry. From this case study it is possible to demonstrate the functionality of the BD^2XML and make it a reflection on the design challenges. Therefore, an automatic tool for electronic systems design reduces the time and costs of the design.